2015
DOI: 10.1111/mmi.13015
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the cell division protein GpsB regulates PrkC kinase activity through a negative feedback loop in Bacillus subtilis

Abstract: SummaryAlthough many membrane Ser/Thr-kinases with PASTA motifs have been shown to control bacterial cell division and morphogenesis, inactivation of the Ser/Thr-kinase PrkC does not impact Bacillus subtilis cell division. In this study, we show that PrkC localizes at the division septum. In addition, three proteins involved in cell division/elongation, GpsB, DivIVA and EzrA are required for stimulating PrkC activity in vivo. We show that GpsB interacts with the catalytic subunit of PrkC that, in turn, phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 41 publications
(89 reference statements)
5
86
0
Order By: Relevance
“…Curiously, the ZipA requirement for preseptal peptidoglycan synthesis can be bypassed by FtsA*, suggesting that assembly state of FtsZ may ultimately govern this activity. In low-GC Gram-positive species such as B. subtilis , EzrA plays an indirect role in recruitment of PBPs 22,99 , which is tied to post-translational regulation via the serine-threonine protein kinase family member PrkC 100102 .…”
Section: Divisome Maturation and Cytokinesismentioning
confidence: 99%
“…Curiously, the ZipA requirement for preseptal peptidoglycan synthesis can be bypassed by FtsA*, suggesting that assembly state of FtsZ may ultimately govern this activity. In low-GC Gram-positive species such as B. subtilis , EzrA plays an indirect role in recruitment of PBPs 22,99 , which is tied to post-translational regulation via the serine-threonine protein kinase family member PrkC 100102 .…”
Section: Divisome Maturation and Cytokinesismentioning
confidence: 99%
“…Perhaps the gpsB null phenotype of phosphomimetic mutations reflects the introduction of a net negative charge in this region affecting the ability of GpsB to interact with PrkC or another divisome component. A molecular rationale for the gpsB null phenotype associated with the phosphomimetic mutation reported earlier 19 and herein remains to be determined.…”
Section: Discussionmentioning
confidence: 88%
“…19 The phosphomimetic mutations T75D and T75E appeared to have the same salt-sensitive phenotype as a gpsB deletion. 19 Likewise, we found that the introduction of the analogous T88D exchange into Lm GpsB almost completely inactivated the protein. However, the phosphoablative T88A mutation was without effect on complementation activity of Lm GpsB (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations